Critical Elements of Shariah-Compliant Hotels: A Case Study of Malaysia - BINTI ABD RAHMAN, SITI NUR HUSNA; Mohd Azli, Rafidah; Mohd Zhaffar, Nursafra (Human Sustainability Procedia, 2025)
The Islamic hospitality industry in Malaysia is experiencing significant growth in line with increasing demand for Shariah-compliant services. This article explores the essential elements required for a Shariah-compliant hotel based on Islamic principles and the needs of Muslim travelers. The study adopts a qualitative approach using document analysis and literature review, supported by selected case studies in Malaysia. Findings reveal that gender segregation, provision of halal food, prohibition of non-Shariah-compliant activities, and staff training based on Islamic values are among the critical elements that must be emphasized. This study offers implications for policymakers, hoteliers, and authorities in enhancing the implementation guidelines for Shariah-compliant hotels in Malaysia.